2015
DOI: 10.1016/s1995-7645(14)60351-5
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Profilin—1 in regulating eNOS/NO signaling pathway and its role in hypertensive myocardial hypertension

Abstract: Profilin-1 expression, being negative in regulating Caveolin-3 expression and eNOS/NO pathway activity, promotes the development of myocardial hypertrophy which can be reversed by Profilin-1 silencing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Several studies have suggested PFN1 to be a critical promoter of cardiac hypertrophy. Expression of PFN1 could inhibit the expression of caveolin-3 and the activity of eNOS/NO pathway, exerting a promotion effect to the development of hypertensive cardiac hypertrophy[ 74 ]. PFN1 expression is significantly enhanced in human atherosclerotic plaques and the serum levels of PFN1 correlate with the degree of atherosclerosis in humans [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested PFN1 to be a critical promoter of cardiac hypertrophy. Expression of PFN1 could inhibit the expression of caveolin-3 and the activity of eNOS/NO pathway, exerting a promotion effect to the development of hypertensive cardiac hypertrophy[ 74 ]. PFN1 expression is significantly enhanced in human atherosclerotic plaques and the serum levels of PFN1 correlate with the degree of atherosclerosis in humans [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these studies suggest that biomechanical and metabolic abnormalities relevant to vascular disease elicit the upregulation of profilin‐1, which in turn could integrate these signs into remodelling of EC cytoskeleton. More recently, studies focused on the association between profilin‐1 and atherosclerotic vascular diseases including hypertension and coronary artery disease . Caglayan et al showed that profilin‐1 expression is significantly enhanced in human atherosclerotic plaques compared to normal vessel wall and the serum levels of profilin‐1 correlated with the degree of atherosclerosis in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Ramaiola et al studied profilin‐1 in patients with myocardial infarction and reported that profilin‐1 is secreted from fully activated platelets in the thrombotic mass in coronary arteries and detected in systemic circulation that may be a potential marker of thrombosis. In addition, Liang et al demonstrated that reduced profilin‐1 provides to stabilize blood pressure and improvement in myocardial hypertrophy in a hypertensive mouse model . However, the data about profilin‐1 in CKD population are lacking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiac hypertrophy is an adaptive response to sustained hypertension, and there is also evidence for elevated Pfn1 expression in the hypertrophic myocardium of SHR rats (Zhao et al, 2013b). Furthermore, myocardial hypertrophy is promoted by adenoviral overexpression of Pfn1 (Kooij et al, 2016) and, conversely, limited by Pfn1 silencing (Xia et al, 2015). It is also important to note that in acute myocardial infarction (a potential complication of hypertension), elevated levels of Pfn1 are secreted when platelets aggregate in the coronary thrombus, and this level of secreted Pfn1 increases the longer the thrombus is occluded (Ramaiola et al, 2015).…”
Section: Hypertensionmentioning
confidence: 99%